How social movements imagine - Sinha, Bobby Luthra, author.
1 online resource (xiii, 297 pages)
Keywords: "This book examines how micro, contextual issues inspire collective social action forms against everday situations of crises and crimes through an inter-disciplinary, ethnograhic and comparative research conducted among Bishnois and Indian South Africans. Exploring the role of the publics that practice and mobilise their social movement imaginations, the work delves into peoples' ability to move beyond their immediate contexts and politicize multiple social spaces and discursive spheres around them to project their causes. Mapping an anti-poaching movement spearheaded by the Bishnois of western Rajasthan in India and, an anti-substance abuse movement led by the historical Indian diaspora of South Africa, the author argues that such contemporray forms of organised social action replete with alternative frames, symbols and repertoires possess key requisites to be understood as the, 'Newer Social Movements' of the Global South. The volume will be of great interest to scholars and researchers of social and protest movements, migration and diaspora studies, political science, social anthropology, and ethnography"--